Indonesian EFL Students’ Autonomus Learning Implementation in Online Learning - Haryana, Lia; Yudaningrum, Puspita; Hardiyanti, Sri (Universitas Cokroaminoto Palopo, 2023)
Although studies on online learning have been widely discussed, most of the studies still focus on the students’ experiences adjusting to online learning. However, few studies have analyzed students’ experiences in online learning regarding autonomous learning implementation. This study aimed at identifying Indonesian EFL students' autonomous learning implementation in online learning. A questionnaire adapted from Khotimah et al. (2019) and Hidayati and Husna (2020) was used as a single instrument to obtain data from EFL students from 22 universities around Indonesia. This study sample was selected using a random sampling technique, and the data was analyzed using a simple percentage statistics formula. The results showed how students learned English online in four areas: listening, reading, speaking, and writing. They also showed how the students felt about online learning on their own. These experiences relate to students’ experiences selecting learning materials and learning activity preferences. These preferences are divided into learning English for academic purposes and learning English for pleasure. However, regarding students’ efforts to foster their autonomous online learning, the students had implemented three categories of autonomous learning, namely the initiating process, monitoring process, and evaluating process in their learning process. Hence, the research results are expected to provide new insights for the readers about implementing online learning, which can support the students to be more autonomous learners.